2016
DOI: 10.1177/1077801216642870
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Partner Violence in 51 Societies

Abstract: Sexist attitudes have been claimed to play an important role in acceptability of intimate partner violence (IPV). Empirical evidence suggests that sexist individuals are also more accepting of violence in social relationships than non-sexist individuals. Results from multilevel regression models of data from 72,730 respondents of 51 countries around the world showed that (a) both sexism and acceptability of general violence in social relationships were positively related to acceptability of IPV and (b) the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
49
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 44 publications
(73 reference statements)
13
49
0
3
Order By: Relevance
“…Finally, Study 1 proved the influence of ideological variables on social perception of controlling behaviors exercised against one's partner, which substantiated Hypothesis 3. According to initial predictions, a high degree of hostile sexism predicted a greater justification of violent behavior and a lower perceived risk of dating violence, replicating the findings by Herrera et al (2012) and Herrero et al (2017). On the other hand, in agreement with the results by Martín-Fernández, and Waltermaurer (2012), high scores for A-IPVAW predicted a greater justification of violent behavior, a lower perceived severity, as well as a lower perceived risk of suffering dating violence.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, Study 1 proved the influence of ideological variables on social perception of controlling behaviors exercised against one's partner, which substantiated Hypothesis 3. According to initial predictions, a high degree of hostile sexism predicted a greater justification of violent behavior and a lower perceived risk of dating violence, replicating the findings by Herrera et al (2012) and Herrero et al (2017). On the other hand, in agreement with the results by Martín-Fernández, and Waltermaurer (2012), high scores for A-IPVAW predicted a greater justification of violent behavior, a lower perceived severity, as well as a lower perceived risk of suffering dating violence.…”
Section: Discussionsupporting
confidence: 83%
“…Different authors agree that ambivalent sexism is positively related to justification of violent attitudes against the partner in the traditional context (Herrera, Expósito, & Moya, 2012;Herrero, Rodríguez, & Torres, 2017;Valor-Segura, Expósito, & Moya, 2011) and victim-blaming (Gracia, García, & Lila, 2014; Martín-Fernández, Gracia, & Lila, 2018; Vidal-Fernández & Megías, 2014). Furthermore, an association has been found between acceptability of intimate partner violence against women (IPVAW) and perpetration of it (Copp, Giordano, Longmore, & Manning, 2016;Gracia, Rodríguez, & Lila, 2015), so high grades of acceptability of IPVAW increase the likelihood that men exercise violence in the couple and that this violence will be justified and normalized by victims (Martín-Fernández, Gracia, Marco et al, 2018;Waltermaurer, 2012).…”
Section: Sexist Attitudes and Myths About Romantic Lovementioning
confidence: 99%
“…The fact that the current results emerged across a large sample involving wellfunctioning couples living in egalitarian societies illustrates the pervasive impact that hostile sexism has on couples' lives. The negative effects of hostile sexism appear consistent across nations (Glick et al, 2000(Glick et al, , 2002(Glick et al, , 2004Herrero, Rodr ıguez & Torres, 2016) and thus we expect the results to replicate in less egalitarian countries, although they may be exacerbated in different social contexts. For example, the association between male partners' hostile sexism and women's relationship problems may be more pronounced in less egalitarian societies where hostile sexism is more prevalent, gender roles are more rigid, and there is a greater emphasis on men's power (Glick et al, 2000).…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 82%
“…Perceived severity of IPVAW has been negatively related to acceptability of IPVAW (Gracia & Herrero, 2006a;Taylor & Sorenson, 2005). Sexist attitudes have been found to be closely related to attitudes toward IPVAW (Flood & Pease, 2009;Herrero, Rodríguez, & Torres, 2017;Lila, Gracia, & García, 2013). On the other hand, gender is one of the more consistent predictors of attitudes toward IPVAW, with research showing greater justification and acceptability of IPVAW among men; and regarding age, research suggests that attitudes supporting the use of IPVAW tend to be more prevalent among older people (Carlson & Worden, 2005;Fincham et al, 2008;Gracia & Tomás, 2014).…”
Section: The Present Studymentioning
confidence: 93%
“…Our results also revealed that respondents with higher levels of acceptability presented higher scores of ambivalent sexism, in particular in the hostile sexism subscale. Sexism has also been previously related to attitudes justifying IPVAW (e.g., Glick et al, 2002;Herrera, Expósito & Moya, 2012;Herrero et al, 2017;Valor-Segura, Expósito, & Moya, 2011).…”
Section: Discussionmentioning
confidence: 99%